Pengaruh Profitabilitas, Free Cash Flow, Ukuran Perusahaan Dan Kebijakan Dividen Terhadap Nilai Perusahaan (Studi Kasus Pada Sub Sektor Perbankan Yang Terdaftar Di BEI 2017-2021) - Reza Nurfaradila; Muslimin Muslimin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine and analyze the effect of profitability, free cash flow, firm size and dividend policy on firm value. The population in this study were 46 companies registered on the IDX and using a purposive sampling technique, a sample of 10 companies was obtained and there were 5 periods starting from 2019 to 2021, a total sample of 50 is obtained. From the analysis of the results of the research, it shows that profitability and company size affect firm value and free cash flow and dividend policy do not affect firm value. Then the F test simultaneously shows that the variable profitability, free cash flow, company size and dividend policy together have a significant effect on firm value Keywords: Profitability, Free Cash Flow, Company Size, Dividend Policy, Firm Value.